The mirror and the mask : the quest for meaning and identity in 'Kierkegaard's tragic theatre' - Van Heerden, Willem Adriaan (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1997.